Представление длинных упругих канатов в системах автоматического регулирования - Бейнарович В. А. Владислав Александрович; Бородин А. Г.; Кожуховский А. Д.; Копанев С. А.; Удут Л. С. Леонид Степанович (1975, 1975)
Заглавие с титульного листа